2015
DOI: 10.1097/aln.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Adaptive Support Ventilation Mode to Wean Patients after Fast-track Cardiac Valvular Surgery

Abstract: Adaptive support ventilation reduces ventilation time by more than 2 h in patients who have undergone fast-track cardiac valvular surgery while reducing the number of manual ventilator changes and alarms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
1
40
1
4
Order By: Relevance
“…In this meta-analysis, in terms of effectiveness, early tracheal extubation can signi cantly reduce the length of stay in ICU and slightly reduced the average hospital stays. As for security, compared with previous meta-analysis [11,13], the risk of re-intubation in the early extubation group is signi cantly higher than in the conventional extubation group. Seven of the ten studies reporting re-intubation risk reported a higher risk of extubation than the conventional extubation group.…”
Section: Discussionmentioning
confidence: 68%
“…In this meta-analysis, in terms of effectiveness, early tracheal extubation can signi cantly reduce the length of stay in ICU and slightly reduced the average hospital stays. As for security, compared with previous meta-analysis [11,13], the risk of re-intubation in the early extubation group is signi cantly higher than in the conventional extubation group. Seven of the ten studies reporting re-intubation risk reported a higher risk of extubation than the conventional extubation group.…”
Section: Discussionmentioning
confidence: 68%
“…[13] Other pressure modes of mechanical ventilation may have better patient-ventilator synchrony and adequate gas exchange and less ventilator-induced lung injury. [5141516]…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Zhu et al . 1 on adaptive support ventilation, the compared postoperatively physician-controlled ventilation using synchronized intermittent mandatory ventilation with pressure support to closed-loop adaptive support ventilation in patients undergoing fast-track cardiac valvular surgery. Adaptive support ventilation significantly decreased weaning time in these patients by more than 2 h. This was a randomized unblinded trial of patients in a single hospital, and the sample size was modest.…”
Section: Modes Of Mechanical Ventilationmentioning
confidence: 99%
“…Adaptive support ventilation significantly decreased weaning time in these patients by more than 2 h. This was a randomized unblinded trial of patients in a single hospital, and the sample size was modest. Nonetheless, the adaptive support ventilation, a “closed-loop mode, where the ventilator computer adjusts the inspiratory pressure to a tidal volume that minimizes the work of breathing and switches between control and support breaths based on the absence or presence of spontaneous breath efforts,” 1 was superior in getting patients’ tracheas extubated faster, without increasing complications, including reintubations. Once again, physicians are documented to be less efficient than a protocol 2 and as noted by the authors, synchronized intermittent mandatory ventilation has never been documented to be a superior mode of ventilation.…”
Section: Modes Of Mechanical Ventilationmentioning
confidence: 99%